Have the Best Interests of the Child Been Ensured in a Natural Disaster? The Case of the February 6, 2023 Earthquake in Turkey - AYDOS, EMİNE HANDE; YAĞAN, SEVCAN; Alabay, Erhan; DEMİR, GÜL (Springer, 2025)
Adults such as child's parents, caregivers or child development specialists and teachers around the child will reduce the negative situations and the risk of maltreatment that the child will face. This study is aiming to reveal the experiences of preschool teachers and child development specialists who work voluntarily with children in the earthquake area, interacted with and supported children after the earthquake on February 6, 2023 about child rights and children's welfare. This study is basic qualitative research and gathered data from four child developers and four preschool teachers. The findings of the study were categorized under the themes of "right to education", "right to shelter", "right to health" and "right to protection". Social systems, which are usually in place to protect children, collapse because of disasters, increasing the risk of rights violations, particularly when it comes to child abuse. It has also been observed that children's rights to participation, access to a suitable education, knowledge, housing, a nutritious diet, and water are at risk due to the vulnerability of children and infrastructure to natural catastrophes. Children need to be taught about natural disaster preparedness, mitigation, prevention, response, and recovery to reduce their vulnerability to disasters, both structural and non-structural safeguards must be put in place. Ensuring a child-centered, rights-based approach in disaster preparedness and response is crucial to safeguarding children's well-being and promoting their resilience in the face of future crises.
Keywords: Child Development Specialist; Child Right; Earthquake; Preschool Teachers